Effect of craniocerebral hypothermia and cell therapy on autonomic nervous system state in rats - Lomakin, Ivan; Mamontov, Viacheslav; Kudokotseva, Olga (Problems of Cryobiology and Cryomedicine, 2026)
This study investigated the eff ects of rhythmic craniocerebral hypothermia (rCCH), administration of cryopreserved nucleated cord blood cells (NCBCs), and their combined application on autonomic regulation of heart rate and arterial blood pressure (BP) parameters in 12 month old spontaneously hypertensive rats (SHRs) with arterial hypertension (AH). A relationship was established between AH and autonomic nervous system imbalance. SHRs demonstrated a shift in heart rate variability (HRV) indices toward enhanced sympathetic activity, which may indicate reduced neurohumoral regulation and signs of overstrain and asthenization within central regulatory structures. On day 7 aft er the combined application of rCCH and NCBCs, the adaptive compensatory capacity of the organism increased signifi cantly. Although these eff ects diminished by day 30, they remained higher compared to the use of each method separately. In addition, unlike the independent application of rCCH or NCBCs, their combined use resulted in a reduction of both systolic and diastolic BP. Probl Cryobiol Cryomed. 2026; 36(2): 128—135